An Exploration on The Diverse Masculine Identities In Octavia Estelle Butler’s Dawn - S. Lavanya (ILN Journal: Indian Literary Narratives, 2024)
Octavia Estelle Butler is one of the foundational figures of Afrofuturism. Afrofuturism is a cultural aesthetic that is used to narrate a story with Afrocentricity at its core. Butler’s Xenogenesis Series (1987–89) opened a wide range of theoretical explorations. It tells the story of the alien race called the Oankali invading Earth to create hybrid children with the survivors of a nuclear war. Dawn is the first novel in the series and introduces Lilith Iyapo, the protagonist of the novel and one of the foundational characters of the series. Lilith is given the responsibility of training the surviving humans to enter into a gene trade with the alien Oankali. Dawn traces Lilith’s journey in the gene trade process. Lilith faces opposition from her fellow humans. All the male characters treat her with contempt since she has assumed the role of their leader. The men cannot merely accept the fact that a woman is in charge of them. The aim of this paper is to analyse the male characters through the lens of R.W. Connell’s Masculinity theory to study the patterns of patriarchy projected in the novel.